Design and Evaluation of Voriconazole Eye Drops for the Treatment of Fungal Keratitis. (29th April 2014) - Malhotra, Sakshi; Khare, Anubha; Grover, Kanchan; Singh, Inderbir; Pawar, Pravin
Abstract : Voriconazole is a novel antifungal agent with excellent broad spectrum activity commercially available for oral and intravenous administration. The purpose of this study was to prepare ophthalmic formulation of hydroxypropyl beta cyclodextrin (HP-β -CD) based voriconazole containing benzalkonium chloride BAK and EDTA with or without viscosity modifiers and study its permeation characteristics through freshly excised goat cornea. The results were observed that viscosity and force of bioadhesion of the voriconazole HP-β -CD solutions containing xanthan gum (XG) are more as compared to polyvinyl alcohol. The results revealed that voriconazole drop containing PVA provided least viscosity and higher corneal permeation of drug, while drop formulated with XG had maximum viscosity and least permeation. The HP-β -CD based voriconazole (1.5%) ophthalmic formulation containing xanthan gum (1.5), preserved with BAK and EDTA, could provide shelf life of 2 years. The microbiological studies showed that voriconazole ophthalmic solution containing xanthan gum shows better antifungal activity as compared to voriconazole and xanthan gum alone. Thus, it can be concluded that HP-β -CD based voriconazole (1.5%, pH 7.0) ophthalmic solution containing BAK and EDTA with viscosity modifier XG provided maximum precorneal residence time as compared to other viscosity modifiers and polyvinyl alcohol provided less precorneal residence time than other viscosity modifiers.